2013
DOI: 10.1016/j.jiph.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B: Report of prevalence and access to healthcare among Chinese residents in Sheffield UK

Abstract: This model of outreach testing is helpful for addressing health inequalities afflicting the UK's Chinese community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…However, other studies have shown no difference in treatment uptake rates among immigrants [79]. Lack of insurance coverage [34] and lack of access to specialist physicians [78] were felt to be barriers to treatment in some studies. Therefore, a concerted system-wide approach is required to identify and treat a significant proportion of migrants with viral hepatitis, in order to reduce the burden of chronic liver disease in this population.…”
Section: Improving Case Identification and Treatment Among Migrantsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, other studies have shown no difference in treatment uptake rates among immigrants [79]. Lack of insurance coverage [34] and lack of access to specialist physicians [78] were felt to be barriers to treatment in some studies. Therefore, a concerted system-wide approach is required to identify and treat a significant proportion of migrants with viral hepatitis, in order to reduce the burden of chronic liver disease in this population.…”
Section: Improving Case Identification and Treatment Among Migrantsmentioning
confidence: 93%
“…Estimates suggest that 31 US outreach programs active in 2008 screened only 21,000 individuals [74]. Studies on viral hepatitis treatment rates and efficacy among immigrants are limited [76][77][78]. One Italian study showed that immigrants were significantly less likely than Italian-born patients to receive HBV antiviral therapy [76].…”
Section: Improving Case Identification and Treatment Among Migrantsmentioning
confidence: 99%
“…Among Asian migrants, it was 0.1% for people born in India, 1.5% for people born in Bangladesh, 1.8% for people born in Pakistan [35], 8.7% for Chinese people [36], and 1.7% among women coming from high prevalence countries [33]. No cases were found among 36 newly arrived migrants who were screened in London, but the sample was too small to draw any conclusion [34].…”
Section: Hepatitis B Virusmentioning
confidence: 95%
“…10 A 2013 UK study demonstrated that 1.1% of tested individuals were positive for HBsAg; 11 in 2009, the prevalence of HBV among migrants in the UK was estimated to be 4%, 12 ranging from 0.1% to 17.4% depending on ethnic group and study method. [13][14][15][16][17][18] In 2012, the National Institute for Health and Care Excellence (NICE) recommended that all people born in a country with HBV prevalence of ≥2% should be offered a HBV test and that testing is offered in primary care. 19 In 2011, approximately 7.5 million (13%) individuals living in England and Wales were born outside of the UK.…”
Section: Introductionmentioning
confidence: 99%